Variation in available shaded area changes behaviour parameters in grazing dairy cows during the warm season - Stivanin, Sheila Cristina Bosco (2019)
The objective was to investigate the effects of available shaded area on behavioural characteristics of lactating cows during the warm season in the subtropics. Twelve Holstein cows were divided into groups, with 2 (SH2) or 10 m2 (SH10) of available shade per cow (six cows per treatment). The behaviour was recorded when animals were grazing from 09.00 to 16.00 h (GMT −02.00 h) throughout the trial. Data considered in the statistical analysis were restricted to the five days when the maximum temperature was ≥ 25 °C. Cows in the SH10 group had lower panting score, but higher proportions of time in shade and lying down and stayed more time per visit in the shaded area than cows in the SH2 group. Cows in the SH10 group had less events of competition near the water trough and in the shaded area than cows in the SH2 group. The solar radiation threshold that triggered the use of the shade was lower in SH10 than in SH2 group. Hourly proportion of time spent grazing or ruminating differed between shaded areas at specific times. The 2 m2 of available shaded area per cow is sufficient for all cows to enter the shaded area at the same time. In spite of that, 2 m2 of available shaded area per cow negatively affects the proportion of time spent lying and in the shaded area; in addition, it enhances agonistic behaviours between cows when compared with 10 m2 of shade per cow